2011
DOI: 10.1371/journal.pone.0017015
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Perchlorate Exposure Biomarkers in a Highly Exposed Population: A Pilot Study

Abstract: Exposure to perchlorate is ubiquitous in the United States and has been found to be widespread in food and drinking water. People living in the lower Colorado River region may have perchlorate exposure because of perchlorate in ground water and locally-grown produce. Relatively high doses of perchlorate can inhibit iodine uptake and impair thyroid function, and thus could impair neurological development in utero. We examined human exposures to perchlorate in the Imperial Valley among individuals consuming loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…17,26,30,[45][46][47] The adolescent and adult food models also show that consumption of vegetables and fruits were significant sources of perchlorate, which is consistent with earlier studies. 21,22,44 In addition, the contribution of dark-green leafy vegetables, which was significant in the adult food model, is well-supported by other studies. 11,22,27,28 Although egg consumption was a significant predictor of increased urinary perchlorate on a unit mass basis in the adult food model, it did not contribute to perchlorate exposure in the median diet because the median mass consumed was zero (Table 3), 21 likewise reported that perchlorate in eggs contributes minimally to average perchlorate intakes in the United States.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…17,26,30,[45][46][47] The adolescent and adult food models also show that consumption of vegetables and fruits were significant sources of perchlorate, which is consistent with earlier studies. 21,22,44 In addition, the contribution of dark-green leafy vegetables, which was significant in the adult food model, is well-supported by other studies. 11,22,27,28 Although egg consumption was a significant predictor of increased urinary perchlorate on a unit mass basis in the adult food model, it did not contribute to perchlorate exposure in the median diet because the median mass consumed was zero (Table 3), 21 likewise reported that perchlorate in eggs contributes minimally to average perchlorate intakes in the United States.…”
Section: Discussionsupporting
confidence: 75%
“…The milk products food group was significantly associated with increased urinary perchlorate in the food models, which is consistent with studies of perchlorate exposure from dairy products. 18,21,43,44 Perchlorate can bioaccumulate in milk because perchlorate absorbed from consumption of forage crops is actively transported during lactation by the sodium-iodide symporter present in the mammary gland. 17,26,30,[45][46][47] The adolescent and adult food models also show that consumption of vegetables and fruits were significant sources of perchlorate, which is consistent with earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…That the adjusted GM urinary perchlorate was highest in Hispanic compared to other racial/ethnic categories is likely the result of dietary differences, but the small subsample size limited further analysis. The highest adjusted urinary perchlorate concentrations were observed in winter, possibly because fresh vegetables available and consumed at that time of year came from arid regions where perchlorate from natural and anthropogenic sources result in higher food crop levels (English et al, 2011; Sanchez et al, 2008 and 2009). Leafy green vegetable intake was predictive of urine SCN, consistent with the observation that various foods, including root and cruciferous vegetables (e.g., kale, broccoli, cauliflower) contain SCN or cyanide that is subsequently metabolized to SCN (Clements, 1960).…”
Section: 0 Discussionmentioning
confidence: 99%
“…In all instances, water concentrations are converted (where necessary) to Average Daily Rate of Intake (ADRI) by use of the age-specific body weights and water ingestion rates used in Crawford-Brown [18] for the perchlorate Monte Carlo analysis performed in that paper. For studies using urinary perchlorate as the exposure metric, the conversion to dietary intake rate uses the results of Leung et al [54], English et al [55] and Lau et al [56], with a mean conversion factor of 0.015 µg/kg-day per µg/L(urine). These conversions allow comparison with the results of Greer et al [14] summarised in Figure 1 by expressing all exposures in units of ADRI, although note should be taken of the differences between the dosing regime and timing of measurements of the Greer et al [14] and the large majority of epidemiological studies (the latter being primarily chronic exposures at environmentally relevant dose-rates).…”
Section: ) Mendez and Eftimmentioning
confidence: 99%